Molecular targets of 5-fluoroorotate in the human malaria parasite, Plasmodium falciparum. - Rathod, P K (1992)
5-Fluoroorotate is known to have potent antimalarial activity against chloroquine-susceptible as well as chloroquine-resistant clones of Plasmodium falciparum. It was hypothesized that this activity was mediated through synthesis of 5-fluoro-2'-deoxyuridylate, an inactivator of thymidylate synthase, or through incorporation of 5-fluoropyrimidine residues into nucleic acids. Treatment of P. falciparum in culture with 100 nM 5-fluoroorotate resulted in rapid inactivation of malarial thymidylate synthase activity. A 50% loss of thymidylate synthase activity as well as a 50% decrease in parasite proliferation were seen with 5 nM 5-fluoroorotate. Dihydrofolate reductase activity, which resides on the same bifunctional protein as thymidylate synthase, was not affected by 5-fluoroorotate treatment. Incubation of malarial parasites with 3 to 10 microM radioactive 5-fluoroorotic acid for 48 h resulted in significant incorporation of radioactivity into the RNA fraction of P. falciparum; approximately 9% of the uridine residues were substituted with 5-fluorouridine. However, compared with the 50% inhibitory concentrations of 5-fluoroorotate, a 1,000-fold higher concentration of the pyrimidine analog was required to see significant modification of RNA molecules. Results of these studies are consistent with the hypothesis that thymidylate synthase is the primary target of 5-fluoroorotate in malarial parasites.